2020
DOI: 10.1051/0004-6361/201937155
|View full text |Cite
|
Sign up to set email alerts
|

Environmental processing in cluster core galaxies at z = 1.7

Abstract: Today, the brightest cluster galaxies (BCGs) are passive and very massive galaxies at the center of their clusters, and they still accrete mass through swallowing companions and gas from cooling flows. However their formation history is not well known. We report CO(4→3) and continuum map observations of the SpARCS1049+56 BCG at z = 1.709, one of the most distant known BCGs. Our observations yield M H 2 < 1.1 × 10 10 M for the BCG; while in CO(4→3), we detect two gas-rich companions at the northeast and southea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 73 publications
5
19
0
Order By: Relevance
“…A large reservoir (∼ 10 11 M ) of molecular gas was detected, likely associated with a number of cluster core BCG companions, unresolved by the LMT, within the large 25 arcsec diameter (i.e., ∼ 200 kpc at z = 1.7). Our recent NOEMA observations (Castignani et al 2020b) confirmed this scenario, with the detection of two gas-rich BCG companions within 20 kpc from the BCG, and allowed us to set a robust upper limit to the molecular gas reservoir M H 2 < 1.1 × 10 10 M .…”
Section: Distant Bcgs Observed In Cosupporting
confidence: 61%
“…A large reservoir (∼ 10 11 M ) of molecular gas was detected, likely associated with a number of cluster core BCG companions, unresolved by the LMT, within the large 25 arcsec diameter (i.e., ∼ 200 kpc at z = 1.7). Our recent NOEMA observations (Castignani et al 2020b) confirmed this scenario, with the detection of two gas-rich BCG companions within 20 kpc from the BCG, and allowed us to set a robust upper limit to the molecular gas reservoir M H 2 < 1.1 × 10 10 M .…”
Section: Distant Bcgs Observed In Cosupporting
confidence: 61%
“…Such features may have suggested that the intense starbursting occurring in SpARCS1049 is being driven by a merger-like event, but an extremely large molecular gas reservoir of 1.1±0.1×10 11 M e was also detected in the core (Webb et al 2017) and showed no signs of multiple velocity peaks as would be expected in a major merger event (Gao et al 2001;Greve et al 2005;Schulz et al 2007). Recently, these features were also interpreted as evidence of ram pressure stripping occurring in the cluster core (Castignani et al 2020).…”
Section: Ir 12mentioning
confidence: 85%
“…Recently, Castignani et al (2020) obtained NOEMA CO(  4 3) and continuum map observations of SpARCS1049. They detected two sources within 20 kpc of the BCG: the first appeared to be associated with a pair of merging cluster galaxies, while the second showed evidence of a CO(  4 3) tail and was interpreted as evidence for ram pressure stripping.…”
Section: Runaway Gas Cooling As the Source Of The Starburstmentioning
confidence: 99%
“…This gas component is one of the most massive reported so far for an HzRG nucleus in an overdense region. Other examples of large gas reservoirs detected around similar objects are the Spiderweb (∼2 × 10 10 (α CO /0.8) M at z = 2.2; Emonts et al 2018), SpARCS J1049+56 (M H 2 ∼ 1 × 10 11 (α CO /0.8) M at z = 1.7; Webb et al 2017; see also Castignani et al 2020), and Candels-5001 (M H 2 ∼ 2−6 × 10 11 (α CO /10) M at z = 3.47; Ginolfi et al 2017) BCGs.…”
Section: Frii Host Galaxymentioning
confidence: 96%